Community based distribution agents’ approach to provision of family planning information and services in five Nigerian States: A mirage or a reality? (2011)
Background: Reducing maternal mortality in Nigeria has received continuous attention both nationally and internationally. Objectives: This article highlights the outcome of an intervention which sought to address maternal mortality reduction through increasing contraceptive uptake in 10 rural local government areas (LGAs)in five Nigerian states. Method: The community based distribution (CBD) approach was used in the implementation of a three year intervention that targeted 10 LGAs. Two hundred and fifty community members were trained as community based distribution agents (CBDA) to provide information on reproductive health, provide non-prescriptive family planning (FP) commodities, treat minor aliment and make referrals to primary health centres within the communities. Results: Final evaluation revealed an increase in the proportion of community members who had utilised FP commodities at all, from 28% at baseline to 49%, and an increase in the proportion of current contraceptive users from 16% at baseline to 37%. An average of 50% increase in clientele patronage was also observed in the 10 LGAs’ primary health care centres. Most (96%) of the interviewed CBDA agents reported that a drug-revolving system was in place to ensure that drugs and commodities were available. On-the-spot assessment of the service forms revealed that 86% of them had their activities regularly recorded in their worksheets. Some of the challenges faced by CBDA were discrimination and misconception of community members about family planning (38%), inadequate financial support (14%), and transportation problems (8%). Conclusion: This study has demonstrated that the CBD approach played a critical role in enhancing access to Reproductive Health and Family Planning information and services in the project communities.